Ablation of rat TRPV1-expressing Adelta/C-fibers with resiniferatoxin: analysis of withdrawal behaviors, recovery of function and molecular correlates - Haspel Gal; Madian Nicholas; Navarro Julia; Scholl Lindsey; Lopez Matthew; Keller Jason M; Bates Brian D; Mitchell Kendall; Nemenov Michael I; Iadarola Michael J (SAGE Publishing, 2010)
Abstract Background Ablation of TRPV1-expressing nociceptive fibers with the potent capsaicin analog resiniferatoxin (RTX) results in long lasting pain relief. RTX is particularly adaptable to focal application, and the induced chemical axonopathy leads to analgesia with a duration that is influenced by dose, route of administration, and the rate of fiber regeneration. TRPV1 is expressed in a subpopulation of unmyelinated C- and lightly myelinated Adelta fibers that detect changes in skin temperature at low and high rates of noxious heating, respectively. Here we investigate fiber-type specific behaviors, their time course of recovery and molecular correlates of axon damage and nociception using infrared laser stimuli following an RTX-induced peripheral axonopathy. Results RTX was injected into rat hind paws (mid-plantar) to produce thermal hypoalgesia. An infrared diode laser was used to stimulate Adelta fibers in the paw with a small-diameter (1.6 mm), high-energy, 100 msec pulse, or C-fibers with a wide-diameter (5 mm), long-duration, low-energy pulse. We monitored behavioral responses to indicate loss and regeneration of fibers. At the site of injection, responses to C-fiber stimuli were significantly attenuated for two weeks after 5 or 50 ng RTX. Responses to Adelta stimuli were significantly attenuated for two weeks at the highest intensity stimulus, and for 5 weeks to a less intense Adelta stimulus. Stimulation on the toe, a site distal to the injection, showed significant attenuation of Adelta responses for 7- 8 weeks after 5 ng, or 9-10 weeks after 50 ng RTX. In contrast, responses to C-fiber stimuli exhibited basically normal responses at 5 weeks after RTX. During the period of fiber loss and recovery, molecular markers for nerve regeneration (ATF3 and galanin) are upregulated in the dorsal root ganglia (DRG) when behavior is maximally attenuated, but markers of nociceptive activity (c-Fos in spinal cord and MCP-1 in DRG), although induced immediately after RTX treatment, returned to normal. Conclusion Behavioral recovery following peripheral RTX treatment is linked to regeneration of TRPV1-expressing Adelta and C-fibers and sustained expression of molecular markers. Infrared laser stimulation is a potentially valuable tool for evaluating the behavioral role of Adelta fibers in pain and pain control.